The linkages between water security, conflict, participation, and governance in smallholder irrigation schemes in KwaZulu-Natal, South Africa: a partial least squares structural equation modelling approach - Phali, Lerato; Naidoo, Denver; Mudhara, Maxwell (Frontiers in Water, 2025)
The increasing competition for water resources leads to conflict, as utility-maximizing farmers aim to improve their productivity to enhance food security and economic well-being. Conflicts within Smallholder Irrigation Schemes (SIS) are particularly rife due to inequitable water distribution that stems from various factors, leading to water insecurity. Using a sample of 302 farmers, this study investigated the multiple linkages between irrigation scheme governance, participation in scheme management, conflicts, and water security. The study adopted the Partial Least Squares-Structural Equation Modelling (PLS-SEM) approach to analyze the collective dynamic relationships between conflict, water rights, inclusive governance, and water security in SIS in KwaZulu-Natal Province, South Africa. The findings indicate that perceptions of governance, indicated by fairness in water allocation and enforceable water rules, are negatively related to conflicts in irrigation schemes. Furthermore, farmers who do not experience conflict are more likely to be water-secure. Results also indicate a negative relationship between participation in scheme management and conflict. As such, interventions should be targeted toward enhancing good governance, fostering farmer participation, and improving mechanisms of conflict management in SIS. This can be achieved by decentralizing decision-making to include farmers in rule enforcement, leveraging existing traditional authority structures to enhance legitimacy. The development of longitudinal datasets is also needed to track water adequacy, conflict trends, and governance efficacy to inform adaptive management to ensure water security.